The Benefits of Being Proactive While Working Remotely: Leveraging Self-Leadership and Job Crafting to Achieve Higher Work Engagement and Task Significance - Costantini, Arianna; Weintraub, Jared (Frontiers in Psychology, 2022)
Given the growing number of remote and hybrid working arrangements, this research investigates the process and outcomes of proactivity during remote work. We approach proactivity during remote working as a resource-building process and integrate self-leadership and job crafting literature. We propose that employees’ self-leadership allows them to regulate their resources optimally- enabling resource availability that can be used to arrange remote working demands and resources proactively. We collected three-wave data from remote workers (n = 329 observations) and tested our hypotheses using multilevel analyses. Results differed by level of analysis. Specifically, when comparing behaviors between participants (i.e., the between-level), social expansion mediated the relationship between self-goal setting and task significance. In contrast, at the within-level (i.e., analyzing differences in behavior within the same person), social expansion mediated the relationship between self-goal setting and work engagement. Overall, these findings suggest that self-leadership allows higher availability of resources- enabling the proactive initiation of social interactions, which, at the within level enhance work engagement and at the between level improve task significance during remote work. We discuss these findings considering the implications to design interventions to foster more positive remote-work experiences.